Correlation of Knowledge and Beliefs to Adherence with Antibiotic Use in Adult Patients at a Private Hospital in Sidoarjo - Wattiheluw, Muhammad Hasan; Herawati, Fauna; Setiasih, Setiasih; Yulia, Rika (Kesmas, 2020)
Infectious diseases are one of the top ten causes of death in the world. Antibiotic therapy is administered for infectious diseases, but if bacteria are exposed to antibiotics continuously, then the bacteria are able to adapt to the medication, thereby resulting in antibiotic resistance. This condition results in an increase in mortality, long hospitalization period, and increased cost of antibiotic therapy and health services. Adherence to using antibiotics may be influenced by knowledge and beliefs about them. This study aimed to understand correlation between knowledge and belief with adherence to antibiotic use at a private hospital in Sidoarjo. This cross-sectional study, the data collected in three months period, was conducted with a questionnaire for assessment knowledge and belief. A pill count method was applied for assessment adherence to using antibiotics prescribed by doctors. The study results show that knowledge of the respondents was adequate for 76 people (69.7%), belief was adequate for 74 people (67.9%), and adherence to antibiotic use for 79 people (72%). Regression analysis showed that the variable that significantly influenced the adherence of patients in using antibiotics was perceived threat (p-value = 0,029). Sex, age, education, income, occupation, and marital status have no contribution to antibiotic knowledge, belief, and adherence.